2013
DOI: 10.1016/j.celrep.2013.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria Coordinate Sites of Axon Branching through Localized Intra-axonal Protein Synthesis

Abstract: SUMMARY The branching of axons is a fundamental aspect of nervous system development and neuroplasticity. We report that branching of sensory axons in the presence of NGF occurs at sites populated by stalled mitochondria. Translational machinery targets to presumptive branching sites, followed by recruitment of mitochondria to these sites. The mitochondria promote branching through ATP generation and the determination of localized hotspots of active axonal mRNA translation, which contribute to actin-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
336
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 247 publications
(355 citation statements)
references
References 40 publications
18
336
1
Order By: Relevance
“…This finding would suggest that reduced target innervation is the detrimental consequence of mitochondrial dysfunction and cytoskeletal disruption. These data are supported by the finding that mitochondria are required to initiate and maintain the formation of axonal branches in DRG neurons (42); the ability to extend and retract branches dynamically is integral to the navigation of axons toward their targets. Furthermore, restoration of actin network function could improve neuronal survival, because actin dynamics mediate vesicle transport and are required specifically for the TrkA/NGF endosomal retrograde survival signaling in DRG neurons (53) that is necessary to prevent the default apoptotic response (46).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This finding would suggest that reduced target innervation is the detrimental consequence of mitochondrial dysfunction and cytoskeletal disruption. These data are supported by the finding that mitochondria are required to initiate and maintain the formation of axonal branches in DRG neurons (42); the ability to extend and retract branches dynamically is integral to the navigation of axons toward their targets. Furthermore, restoration of actin network function could improve neuronal survival, because actin dynamics mediate vesicle transport and are required specifically for the TrkA/NGF endosomal retrograde survival signaling in DRG neurons (53) that is necessary to prevent the default apoptotic response (46).…”
Section: Discussionsupporting
confidence: 70%
“…Axonal branching is a key component of normal axon outgrowth during development (42). Microtubule invasion is a prerequisite for branch stabilization but is dependent on the local aggregation of mitochondria at branch points (42). To explore branch composition further, we analyzed the distribution of mitochondria at axonal branch points.…”
Section: Bgp-15 Normalizes Impaired Actin Dynamics In Ikbkapmentioning
confidence: 99%
“…Another possibility is that not all filopodia are being actively elongated or fail to continue to mature. In support of this, it has been shown that mitochondria stalling at the axon branching sites are necessary for efficient branching, an actinpolymerization-dependent process (Spillane et al, 2013). However, we cannot exclude a role for mitochondria in filopodial Ca 2+ regulation (Davenport et al, 1996) or other signaling events leading to filopodia formation.…”
Section: Discussionmentioning
confidence: 89%
“…The role of energy production in pathologies related to neuronal development A growing volume of evidence suggests that impaired mitochondrial function may lead to a disruption in normal neural plasticity and reduce cellular resilience (Li et al, 2004;Quiroz et al, 2008;Ruthel and Hollenbeck, 2003;Spillane et al, 2013), which may in turn promote the development or progression of mood and psychotic disorders. Indeed, in many diseases in which mitochondrial defects are present there is high incidence of psychiatric comorbidities.…”
Section: Do Neurons Have a Mechanism To Sense Upcoming Energy Needs?mentioning
confidence: 99%